Contribution of attachment in children’s separation anxiety - Mofrad, Sakineh; Abdullah, Rohani; Uba, Ikechukwu (Universiti Putra Malaysia Press, 2012)
Literature suggests that child attachment and anxiety symptoms are related. The purpose of the present study was to assess whether attachment patterns related differently to separation anxiety symptoms (fear of being alone, and fear of abandonment). Three attachment patterns assessed were secure, avoidant and ambivalent attachment. The findings indicated that ambivalent attachment was related with higher separation anxiety symptoms (r=.57) compared to avoidant attachment (r=.53). More so, ambivalent attachment was also related to the fear of abandonment (r=.52), while avoidant attachment was related with the fear of being alone (r=.63). In conclusion, consistently responsive mothers are always receptive and supportive of their children’s mental health